Intellectual Commons and the Law A Normative Theory for Commons-Based Peer Production - Broumas, Antonios (University of Westminster Press, 2020)
'With clarity and sophistication, Antonios Broumas presents a bold new theory of intellectual commons and powerful arguments for a new body of supportive law. This book not only reveals the misleading logic of intellectual property law in our time; it reveals the rich possibilities for constructive change that legally protected commoning can bring. Highly recommended!' - David Bollier, Director, Reinventing the Commons Program, Schumacher Center for a New Economics. 'Liberating the Intellectual Commons from the fetters of capital accumulation and appropriation, would give us a renaissance of creative energies and empowered communities: exactly what the world needs to move away from the social and ecological devastations of our times. This book is a thoughtful and compelling argument for making this possible through the works of the law and the redesign of public domain as a common space.' - Massimo De Angelis, Professor of Political Economy and Social Change, Co-director of the Centre for Social Justice and Change, University of East London. 'In this pioneering book, Antonios Broumas argues that philosophically, morally, politically and economically we are in urgent need of a new legal regime that recognizes the intellectual commons, peer production and sharing as the primary practices of intellectual production, distribution and consumption. I cannot imagine a more urgent task today. A legally protected intellectual commons will lead to greater scientific and cultural innovation and creativity and will lead to an urgently needed second Enlightenment. This book should be read by lawyers, critical theorists, economists and the many professionals of science, culture and the academy.' - Costas Douzinas, Professor of Law, Birkbeck, University of London. 'Antonios Broumas' book is an excellent critical analysis of the cultural commons and a must-read for everyone interested in understanding what the commons, the cultural commons, and the digital commons are all about. This work brilliantly outlines the foundations of an empirically grounded critical theory of the commons and the cultural commons in the context of the interactions of law and society.' - Christian Fuchs, Professor of Media and Communication Studies, author of Communication and Capitalism: A Critical Theory (2020). 'Broumas takes us on a spellbinding tour of how and why the law could and should change to accommodate the creative multitude, which engages into an emerging mode of production. He tells a vibrant story that makes us shout: "Lawmakers of the world, unite!"' - Vasilis Kostakis, Professor of P2P Governance, Tallinn University of Technology, Faculty Associate at Harvard Law School. At the cutting edge of contemporary wealth creation people form self-governed communities of collaborative innovation in conditions of relative equipotency and produce resources with free access to all. The emergent intellectual commons have the potential to commonify intellectual production and distribution, unleash human creativity through collaboration and democratise innovation with wider positive effects for our societies. Contemporary intellectual property laws fail to address this potential. We are, therefore, in pressing need of an institutional alternative beyond the inherent limitations of intellectual property law. This book offers an overall analysis of the moral significance of the intellectual commons and outlines appropriate modes for their regulation. Its principal thesis is that our legal systems are in need of an independent body of law for the protection and promotion of the intellectual commons, in parallel to intellectual property law. In this context, the author of the book proposes the reconstruction of the doctrine of the public domain and the exceptions and limitations of exclusive intellectual property rights into an intellectual commons law, which will underpin a vibrant non-commercial zone of creativity and innovation in intellectual production, distribution and consumption alongside commodity markets enabled by intellectual property law.